Immunophenotypic Spectrum and Genomic Landscape of Refractory Celiac Disease Type II. (July 2021) - Soderquist, Craig R.; Lewis, Suzanne K.; Gru, Alejandro A.; Vlad, George; Williams, Eli S.; Hsiao, Susan; Mansukhani, Mahesh M.; Park, David C.; Bacchi, Carlos E.; Alobeid, Bachir; Green, Peter H.; Bhagat, Govind
Abstract : Refractory celiac disease type II (RCD II), also referred to as "cryptic" enteropathy-associated T-cell lymphoma (EATL) or "intraepithelial T-cell lymphoma, " is a rare clonal lymphoproliferative disorder that arises from innate intraepithelial lymphocytes. RCD II has a poor prognosis and frequently evolves to EATL. The pathogenesis of RCD II is not well understood and data regarding the immunophenotypic spectrum of this disease and underlying genetic alterations are limited. To gain further biological insights, we performed comprehensive immunophenotypic, targeted next-generation sequencing, and chromosome microarray analyses of 11 RCD II cases: CD4 − /CD8 − (n=6), CD8 + (n=4), and CD4 + (n=1), and 2 of 3 ensuing EATLs. Genetic alterations were identified in 9/11 (82%) of the RCD II cases. All 9 displayed mutations in members of the JAK-STAT signaling pathway, including frequent, recurrent STAT3 (7/9, 78%) and JAK1 (4/9, 44%) mutations, and 9/10 evaluable cases expressed phospho-STAT3. The mutated cases also harbored recurrent alterations in epigenetic regulators ( TET2, n=5 and KMT2D, n=5), nuclear factor-κB ( TNFAIP3, n=4), DNA damage repair ( POT1, n=3), and immune evasion ( CD58, n=2) pathway genes. The CD4 − /CD8 − and other immunophenotypic subtypes of RCD II exhibited similar molecular features. Longitudinal genetic analyses of 4 RCD II cases revealed stable mutation profiles, however, additional mutations were detected in the EATLs, which occurred at extraintestinal sites and were clonally related to antecedent RCD II. Chromosome microarray analysis demonstrated copy number changes in 3/6 RCD II cases, and 1 transformed EATL with sufficient neoplastic burden for informative analysis. Our findings provide novel information about the immunophenotypic and genomic characteristics of RCD II, elucidate early genetic events in EATL pathogenesis, and reveal potential therapeutic targets. Abstract : Supplemental Digital Content is available in the text.